1994
DOI: 10.1111/j.1600-0536.1994.tb02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel release from metals, and a case of allergic contact dermatitis from stainless steel

Abstract: The prevalence of allergic contact dermatitis (ACD) caused by nickel is increasing. The probable cause is the increased use of nickel-containing metals in intimate contact with the skin. The critical factor is the amount of nickel released from these metals (bioavailable nickel) onto the skin. In the present study, we determined, with flame atomic absorbtion spectrometry, the amount of nickel released into synthetic sweat from metal samples. The results of this method were compared with the results of the dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…They also reported a higher prevalence of nickel allergy in girls, which is also reported in other papers [56,57]. Although orthodontic alloys are considered safe, there are case reports on nickel hypersensitivity caused by orthodontic appliances, both from stainless steel and nickel-titanium alloys [50,[58][59][60]. Common intra-oral signs include redness, swelling, and soreness of the oral mucosa and palate, gingiva and lips [59].…”
Section: Corrosion and Elemental Releasesupporting
confidence: 59%
“…They also reported a higher prevalence of nickel allergy in girls, which is also reported in other papers [56,57]. Although orthodontic alloys are considered safe, there are case reports on nickel hypersensitivity caused by orthodontic appliances, both from stainless steel and nickel-titanium alloys [50,[58][59][60]. Common intra-oral signs include redness, swelling, and soreness of the oral mucosa and palate, gingiva and lips [59].…”
Section: Corrosion and Elemental Releasesupporting
confidence: 59%
“…20 The sensitivity of the DMG test has previously been questioned because false-negative reactions have been identified. 19,22,[24][25][26] In case of suspected false-negative DMG reaction, the surface may be pretreated with artificial sweat to dissolve the protective layer. 9,26 Ponka and Ekman 26 demonstrated that 9 (14%) of 66 DMG-negative earrings became DMG positive after treatment with artificial sweat.…”
Section: Discussionmentioning
confidence: 99%
“…cell-mediated hypersensitivity) associated with metal components may be partly responsible for this differential reactivity. The most common orthopaedic soluble metal (ions) sensitizers include nickel, Ni, [16,23,30,35] cobalt, Co, [35] and chromium, Cr, [35] while occasional responses have been reported to tantalum, Ta, [ 11 titanium, Ti, [33,43] and vanadium, V [l]. Nickel is the most common metal sensitizer in humans followed by Co and Cr [2,16,23,30] and cross reactivity between Ni and Co is common [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most common orthopaedic soluble metal (ions) sensitizers include nickel, Ni, [16,23,30,35] cobalt, Co, [35] and chromium, Cr, [35] while occasional responses have been reported to tantalum, Ta, [ 11 titanium, Ti, [33,43] and vanadium, V [l]. Nickel is the most common metal sensitizer in humans followed by Co and Cr [2,16,23,30] and cross reactivity between Ni and Co is common [2]. The incidence of metal sensitivity among the general population is approximately 10% and among patients with well functioning and poorly functioning implants is approximately 25% and 6O%, respectively, in reported compiled analyses of numerous investigations [ 191. What remained poorly characterized were the specific metals that mediate implant related metal hypersensitivity reactions, the incidence of THA metal hypersensitivity using modern immunological testing methods and the relation of metal hypersensitivity to implant performance.…”
Section: Introductionmentioning
confidence: 99%